Hypertension, cardiovascular disease, and nocturia: a systematic review of the pathophysiological mechanisms - Ohishi, Mitsuru; Kubozono, Takuro; Higuchi, Koji; Akasaki, Yuichi (Hypertension research, 2021)
Nocturia significantly impairs quality of life, especially in the elderly population, and urinary retention is a main target of treatment for urologists. In addition to nocturia, cardiovascular diseases are common in the elderly population, and a systematic review showed that hypertension and heart failure are often associated with nocturia. One possible pathogenic mechanism underlying the development of hypertension is an increase in blood pressure due to excessive salt intake in people with high-salt sensitivity. From Guyton's natriuretic curve, we can infer that salt-sensitive hypertensive patients who consume too much salt do not excrete salt during the daytime and are forced to excrete salt at night, resulting in increased urine production and nocturia. In patients with heart failure, the nocturnal supine position leads to an increase in central fluid volume due to an increase in venous return from the periphery, and the secretion of natriuretic peptide is stimulated by the stretching of the atria and ventricles. Thus, natriuresis due to hypertension and hydrodiuresis due to heart failure may cause nocturia, which can effectively be treated by the administration of thiazide diuretics and loop diuretics in the morning, respectively. Because cardiovascular diseases, such as hypertension and heart failure, can cause nocturia and because the treatment methods differ depending on the cause, it is necessary to pay close attention to nocturia in the management of lifestyle-related diseases, such as cardiovascular disease.